Continuous Time Trading in Markets with Adverse Selection - Maarten C.W. Janssen; Vladimir Karamychev (Tinbergen Institute, 2000)
We investigate the nature of the adverse selection problem in a market for adurable goodwhere trading and entry of new buyers and sellers takes place in continuoustime. In thecontinuous time model equilibria with properties that are qualitativelydifferent from thestatic equilibria, emerge. Typically, in equilibria of the continuous timemodel sellers withhigher quality wait in order to sell and wait more than sellers of lower qualitydo. Among other things, we show that for any distribution of quality there exist an infinite number of cyclical equilibria where all goods are traded within a finite time after entering the market.This holds true even if the good is not perfectly durable or when buyers are not risk-neutral.
Keywords: D82; 330; Dynamic Trading; Asymmetric Information; Entry; Durable Goods; Dauerhafte Konsumgüter; Adverse Selektion; Asymmetrische Information; Theorie